Biological potential of Beauveria spp. for the control of Anthonomus eugenii in sweet pepper - Quirós-Campos, Stephanie; Salazar-Castillo, Valerie; Vargas-Martínez, Alejandro (Agronomía Mesoamericana, 2024)
Introduction. Anthonomus eugenii causes considerable economic losses in sweet pepper (Capsicum annuum). Chemical control is ineffective; therefore, it is essential to explore other management alternatives. Objective. To determine the potential of Beauveria spp. strains for the biological control of Anthonomus eugenii in sweet pepper under greenhouse conditions. Materials and methods. The research was conducted between May and August 2023 at the Fabio Baudrit Moreno Agricultural Experimental Station in Alajuela, Costa Rica, in a 96 m2 multispan greenhouse. The evaluated treatments were INTA H-140, INTA H-149, INTA H-168, INTA H-181, and an absolute control, using a completely randomized design with three replications. The number of live adults and infested peppers were quantified weekly. Pearson correlation analysis and repeated measures ANOVA were performed for the evaluated variables. Results. There was an interaction between treatments and days after transplant (dat) for the number of live adults (p < 0.05). INTA H-168 strain significantly reduced the Anthonomus eugenii population in the 60 dat and 64 dat evaluations, with differences of 22.96 and 47.15 adults, respectively. For the variable of the number of infested peppers, there was only an individual effect by dat (p < 0.05). Additionally, a positive correlation was found between the average number of infested peppers and the number of live adults for the 64 dat and 73 dat (p < 0.05). Conclusion. The significant reduction in live adults in the first two evaluations of INTA H-168 strain and its parasitism evidence a biological potential for the control of Anthonomus eugenii.